Penerapan Penyusunan Laporan Keuangan Neraca Berbasis SAK-ETAP Pada UMKM - Cindy Ariesta; Fitriyah Nurhidayah (STIE Muhammadiyah Jakarta, 2020)
The purpose of this study is to find out how and assist in preparing balance sheet financial statements at Elden Coffee Eatery as MSME actors based on SAK-ETAP. This study uses descriptive research method. Sources of data used are secondary data and primary data. The results of this study indicate that the financial statements prepared by researchers based on SAK-ETAP present a balance sheet as an illustration of the business conditions at Elden Coffee Eatery. The balance sheet financial report is prepared based on data and information obtained from the owner of Elden Coffee Eatery in the first quarter (January - April 2020) then processed into a balance sheet financial report according to SAK-ETAP standards.